The intersection of Christian education and philosopher-feminist thought: Addressing child marriage in Indonesia - Munte, Alfonso (HTS teologiese studies, 2025)
One of the global challenges addressed in this article, particularly in the Global South, is the high prevalence of child marriage. The author is situated in an area with one of the highest rates of child marriage in Indonesia. The rationale for selecting this case study is to examine the concept of spiritual freedom and its potential to empower women to challenge the oppression they face with regard to their bodies, rights, and futures. Child marriage should be regarded as a criminal act in the context of Christianity. However, this issue does not appear to be a prominent topic in educational institutions, places of worship, or global discourse. This research employs a qualitative methodology, utilising interview techniques with women who have experienced child marriage. The author then engaged in a process of reflection with feminist philosopher Iris Marion Young, concurrently addressing theological concerns and the role of Christian education. The findings indicate that Christianity and government policy on health are inextricably linked, as health is a divine mandate for humanity to fulfil its responsibilities.Contribution: This article makes a contribution to the field of research in Central Kalimantan and serves to proclaim to the global community that Christian education must address the issue of child marriage as a matter of urgency.